(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify the use of the theoretical framework of Complexity proposed by Edgar Morin in the production of knowledge about nursing care. This is an integrative literature review, carried out in the Virtual Health Library and PubMed databases, from 2009 to 2020. For the selection of articles, the PICo strategy were used. Complete and original articles were included. To assist the analysis of the data, the information was operationalized in the IRAMUTEQ® software. 14 articles were selected, published in national and international journals, with a predominance of qualitative research. After a thorough analysis, two classes originated - Class 1: The Complexity paradigm and nursing care in the face of care adversities. Class 2: Complexity of care in the childhood and adolescence phases. Complexity Theory is used to understand the relationships and phenomena that surround nursing care as a whole.